Review Of The Current Situation Of The Femroacetabular Impingement (Journal of Pharmaceutical Negative Results, 2023)
Femoroacetabular impingement (FAI) is a pathological hip condition characterized by abnormal contact between the acetabulum and femoral head–neck junction. This can occur within the normal physiological range of motion as a result of osseous abnormalities. Types of FAI Cam deformities type (Young men are more prone to be diagnosed with cam impingement) describe an abnormal anterosuperior femoral head–neck junction, whereas pincer deformities Type (Middle-aged women are more common to suffer from pincer impingement and could have comorbidities) describe abnormalities in the shape or orientation of the acetabulum, moreover, some patients have both deformities, designated mixed pathology. Diagnosis of FAI by detailed history collect more data as possible about the patient and his/her pain. And can be diagnosed by physical examination e.g (leg length(LLD), range motion (ROM), Comprehensive provocative tests and radiography(X.ray)). Moreover, pelvis MRI (Magnetic resonance imaging) is mainly used for detecting avascular necrosis, bone marrow edema syndrome, and peritrochanteric space disorders. While the magnetic resonance arthrography (MRA) are the preferred modality for the investigation of intra articular hip pathology, as it provides optimal resolution of soft tissue structures as the labrum, cartilage, joint capsule and ligamentumteres. CT scan can be useful in some instance during the differential diagnosis of a painful hip.It is used to assess the contour of the anterior lateral impingement surface in patients with suspected FAI with good results. Treatment of FAI (Non operative management, Operative management, Open surgical hip dislocation, Combined approach (mini-open arthroscopic assisted, and Arthroscopy).